Clinical and therapeutic relevance of the metabolic oncogene fatty acid synthase in HER2+ breast cancer - Corominas Faja, Bruna (2017)
Fatty acid synthase (FASN) is a key lipogenic enzyme for de novo fatty acid biosynthesis and a druggable metabolic oncoprotein that is activated in most human cancers. We evaluated whether the HER2-driven lipogenic phenotype might represent a biomarker for sensitivity to pharmacological FASN blockade. A majority of clinically HER2-positive tumors were scored as FASN overexpressors in a series of almost 200 patients with invasive breast carcinoma. Re-classification of HER2-positive breast tumors based on FASN gene expression predicted a significantly inferior relapse-free and distant metastasis-free survival in HER2+/FASN+ patients. Notably, non-tumorigenic MCF10A breast epithelial cells engineered to overexpress HER2 upregulated FASN gene expression, and the FASN inhibitor C75 abolished HER2-induced anchorage-independent growth and survival. Furthermore, in the presence of high concentrations of C75, HER2-negative MCF-7 breast cancer cells overexpressing HER2 (MCF-7/HER2) had significantly higher levels of apoptosis than HER2-negative cells. Finally, C75 at non-cytotoxic concentrations significantly reduced the capacity of MCF-7/HER2 cells to form mammospheres, an in vitro indicator of cancer stem-like cells. Collectively, our findings strongly suggest that the HER2-FASN lipogenic axis delineates a group of breast cancer patients that might benefit from treatment with therapeutic regimens containing FASN inhibitors.